Piptolinic acids F–J, five new lanostane-type triterpenoids from Piptoporus betulinus. Issue 21 (2nd November 2019) - Khalilov, Qosimjon; Li, Liya; Liu, Yushuang; Tohtahon, Zeynep; Chen, Xiaoyu; Aisa, Haji Akber; Yuan, Tao
Abstract: Five new lanostane-type triterpenoids, named piptolinic acids F − J (1 –5 ), as well as seven known analogues (6 –12 ), were isolated from methanolic extract of the fruiting bodies of Piptoporus betulinus . Compounds1 –4 were 24-methyl-lanostane triterpenoids, while compound5 was a 3, 4- seco -lanostane derivative. Their structures were established on the basis of extensive spectroscopic analysis (1D, 2D NMR, and HRESIMS). Cytotoxicity evaluation indicated that compound6 exhibited moderate cytotoxic activity against human melanoma cell line A-375 (IC50 = 42.8 μM) and human renal carcinoma cell line 786-O (IC50 = 56.5 μM). Graphical Abstract: